2018
DOI: 10.4187/respcare.05872
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives on Incentive Spirometry Utility and Patient Protocols

Abstract: There was a major discrepancy between health care professionals' beliefs and the published clinical effectiveness data supporting IS. Despite reported adequate education on IS, variability in what health care professionals believed to be appropriate use underscores the literature's lack of standardization and evidence for specific use procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 58 publications
0
24
0
Order By: Relevance
“…Monitoring of vital signs in the post-anesthetic setting is essential to identify patients at potential risk of postoperative respiratory failure [156]. Incentive spirometry is widely used to prevent PPCs, although clinical effectiveness data are limited, and standardized protocols are lacking [157,158].…”
Section: Strength Of Recommendationmentioning
confidence: 99%
“…Monitoring of vital signs in the post-anesthetic setting is essential to identify patients at potential risk of postoperative respiratory failure [156]. Incentive spirometry is widely used to prevent PPCs, although clinical effectiveness data are limited, and standardized protocols are lacking [157,158].…”
Section: Strength Of Recommendationmentioning
confidence: 99%
“…Responses were received from 1,681 unique nurses and RTs from the 4 national organizations with various educational backgrounds, years of experience, and primary practice locations. Respondent characteristics and survey completion rates are fully detailed in Eltorai et al 30 The clear majority of providers agreed that patient adherence with IS is poor (86.0%; 1,416 of 1,647 respon-…”
Section: Resultsmentioning
confidence: 99%
“…Given the lack of standardized protocols for IS use and, therefore, the lack of adherence to such protocols, adherence was deliberately left undefined in the survey to assess providers' real-life perspectives in their own practices. 30 In so doing, the meaning of adherence is standardized to what is actually practiced by providers. An operational definition of adherence is that of a patient acting in accordance with provider advice.…”
Section: Methodsmentioning
confidence: 99%
“…Freitas, et al [12] also revealed no evidence of a difference between groups in the incidence of PPCs with IS and treatment with physical therapy, positivepressure breathing techniques, active cycle of breathing, or preoperative patient education and worse pulmonary function and arterial oxygenation. Eltorai et al [24] investigated the clinical effectiveness of incentive spirometry and found that there was narrow evidence to support its advantages and an absence of harmonized protocol for its use. In addition, Overend,et al [20] conducted a systematic review study and concluded that evidence does not support the use of IS for decreasing the incidence of PPCs.…”
Section: Discussionmentioning
confidence: 99%
“…Freitas, et al, Carvalho et al, Eltorai et al, and Overend et al, have declared that, to date, there is no evidence to support the practice of IS to decrease PPCs. although IS is still usually requested to reduce PPCs, despite the narrow evidence to support its advantages and the absence of a harmonized protocol and they recommend that additional research is necessary to clarify this issue [12,19,20,24]. Agostini and Singh, differ from this opinion and have stated that this practice can improve pulmonary function [25].…”
Section: Introductionmentioning
confidence: 99%